U.S. Physician–Scientist Workforce in the 21st Century: Recommendations to Attract and Sustain the Pipeline. (April 2018) - Salata, Robert A.; Geraci, Mark W.; Rockey, Don C.; Blanchard, Melvin; Brown, Nancy J.; Cardinal, Lucien J.; Garcia, Maria; Madaio, Michael P.; Marsh, James D.; Todd, Robert F.
Abstract : The U.S. physician–scientist (PS) workforce is invaluable to the nation's biomedical research effort. It is through biomedical research that certain diseases have been eliminated, cures for others have been discovered, and medical procedures and therapies that save lives have been developed. Yet, the U.S. PS workforce has both declined and aged over the last several years. The resulting decreased inflow and outflow to the PS pipeline renders the system vulnerable to collapsing suddenly as the senior workforce retires. In November 2015, the Alliance for Academic Internal Medicine hosted a consensus conference on the PS workforce to address issues impacting academic medical schools, with input from early-career PSs based on their individual experiences and concerns. One of the goals of the conference was to identify current impediments in attracting and supporting PSs and to develop a new set of recommendations for sustaining the PS workforce in 2016 and beyond. This Perspective reports on the opportunities and factors identified at the conference and presents five recommendations designed to increase entry into the PS pipeline and nine recommendations designed to decrease attrition from the PS workflow.